Effects of Local Coating on Strengthening and Crack Suppression of Notched PBX Beams. Issue 11 (2nd August 2019) - Wang, Shengnan; Lan, Lingang; Liu, Yangyang; Tang, Mingfeng; Wen, Maoping
Abstract: Notched polymer‐bonded explosive (PBX) structure is a mechanically weak link of a weapon system. In addition to the inherent brittleness and low strength of the PBX material, local stress concentration induced by a notch also threats the structural and functional integrity of a weapon system. In this study, a convenient strengthening method of local coating is newly adopted to the notched region of PBX beams. In virtue of a three‐point bending test and digital image correlation measurement, the effects of local coating on strengthening and crack suppression of the beams are explored. Results demonstrate that, while relieving the stress concentration and improving the load‐carrying capability of the notched beams, the locally applied polymer coating can restrain the crack propagation in the PBX matrix, thus preventing the brittle fracture of the integral structure effectively. These explorations may provide significant inspiration for the potential application of local coating, and at the same time, lay foundation to the performance optimisation of energetic materials. Abstract :